Embodiment of Good Governance through Accountability and Transparency in the Management of Village Fund Allocations - Yusmaniarti Yusmaniarti; Lastini Nur Sholihah; Ummul Khair; Marini Marini (Perkumpulan Dosen Muda (PDM) Bengkulu, 2021)
The Purpose of the this study was to determine the propotional management of Village Fund Allocation (ADD) originating from the Regency APBD, which comes from the portion of the central and regional financial balance funds received by the Regency which is distributed through the village treasury for the empowerment of village communities. Research locations (ADD) are villages located in North Bengkulu Regency, Kec. Padang Jaya with a item of 12 villages. The research was conducted for 4 months, starting from April to July 2020. The sample in the study included 12 village officials in he district. Padang Jaya. Data collection technique using documentation and interviews. The data analysis technique used descriptive and qualitative descriptive data. The results of the research conducted, stated that all villages in the district. Padang jaya, with a total of 12 villages, has implemented the princples of management (ADD) in a transparent, accountable, participatory, orderly manner and budgetary discipline. There 1 village not accountable, as evidenced by the LPPDes Bank book that must be reported to the regent.